Revisión bibliográfica entre HS al 0,10 y carboxi al 0,5 en la reparación de la superficie ocular (2021)
The ocular surface belongs to a delicate portion of the anatomy of the eyeball whose structures have a close relationship with each other to achieve obtain a good homeostasis of the anatomical-functional unit (1). The changes in the ocular surface are associated with inflammatory pathologies at the corneal level, conjunctival, and to some deformations in the corneal structure or alterations of the tear film (2). Objective: To compare the therapeutic action of Hyaluronate of Sodium (HS) and Carboxymethylcellulose (CMC), in the repair of the ocular surface of patients with mild or moderate dry eye. Methods: Literature review in databases such as PubMed/MEDLINE, SCOPUS, Clinical trials, Virtual Library in health, SCIELO, Elservier, between the years 2005 and 2020. Results: A a comparison of the results obtained, observing that the HS is more effective than CMC in resolving signs and symptoms. Conclusions: The HS treatment is more effective than CMC in repairing the surface eyepiece and SOS resolution.